PHAN CHAU TRINH'S THOUGHTS ON ECONOMICS - LESSONS APPLIED TO VIETNAM TODAY - Mai Ước, Trần (International Journal of Psychosocial Rehabilitation, 2021)
Phan Chau Trinh (1872 - 1926), the leader of the Duy Tan movement, with his economic thoughts, has left a bold mark in Vietnam's development history in the late 19th and early 20th centuries. By going through and clarifying the main contents of Phan Chau Trinh's economic thoughts, the article also points out and analyzes the lessons that Vietnam can apply to its renovation, development, and integration processes today.